Analisis Penerapan Tindak Pidana Persiapan dalam Undang-Undang No. 1 Tahun 2023 tentang Kitab Undang -Undang Hukum Pidana - Adabi, Muhammad Ikhwan; Sani, Adam; Zulfikar, Muhammad Nahyan; Jhowanda, Rahmat (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Preparatory criminal acts are actions committed by a person or group of people to plan or prepare a certain criminal act. Even though the actual criminal act has not been committed, these preparatory actions can also be considered a criminal act if they involve elements regulated in criminal law. The problem in this research is what is the difference between preparatory action, trial and initial action of execution as well as analyzing criminal acts of preparatory action in the new Criminal Code. The type of research used is normative legal research, namely legal research carried out by reviewing library materials or secondary data. The results of the research can be concluded that the difference between initial implementation actions and preparatory actions is that preparatory actions are carried out before the start of implementation to prepare the action and not violate the law. Meanwhile, the start of implementation was carried out after preparatory measures and was contrary to the law. So after the enactment of the latest Criminal Code, preparatory acts are no longer seen as acts that are not against the law. Preparatory acts in the latest Criminal Code are considered a separate criminal act. Meanwhile, the urgency of implementing preparations in the latest Criminal Code is the prevention of criminal acts, community protection, prevention, justice, investigation and disclosure.